2020
DOI: 10.3390/min10030211
|View full text |Cite
|
Sign up to set email alerts
|

New Candidate Ultralow-Velocity Zone Locations from Highly Anomalous SPdKS Waveforms

Abstract: Ultralow-velocity zones (ULVZs) at the core–mantle boundary (CMB) represent some of the most preternatural features in Earth’s mantle. These zones most likely contain partial melt, extremely high iron content ferropericlase, or combinations of both. We analyzed a new collection of 58,155 carefully processed and quality-controlled broadband recordings of the seismic phase SPdKS in the epicentral distance range from 106° to 115°. These data sample 56.9% of the CMB by surface area. From these recordings we search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(92 citation statements)
references
References 60 publications
3
80
3
Order By: Relevance
“…Waveforms identified as anomalous all show two arrivals, with the second arrival amplitude approximately equal to or greater than the first arrival. Non-anomalous waveforms in the azimuthal range from 0° to 180° are similar in character to the waveforms labeled as highly anomalous, but do not get labeled as such due to the strict rules imposed in Thorne et al (2020). For example, records at distances approximately less than 110° (Figure 2c) do not have a distinct second arrival, although a second arrival is clearly emerging.…”
Section: ˚mentioning
confidence: 91%
See 3 more Smart Citations
“…Waveforms identified as anomalous all show two arrivals, with the second arrival amplitude approximately equal to or greater than the first arrival. Non-anomalous waveforms in the azimuthal range from 0° to 180° are similar in character to the waveforms labeled as highly anomalous, but do not get labeled as such due to the strict rules imposed in Thorne et al (2020). For example, records at distances approximately less than 110° (Figure 2c) do not have a distinct second arrival, although a second arrival is clearly emerging.…”
Section: ˚mentioning
confidence: 91%
“…These synthetics are computed for a ULVZ with identical properties located on either the source-side ( Figure 3) or receiver-side ( Figure 4) of the path. Using the classification scheme as defined in Thorne et al (2020), highly anomalous recordings are only found for this ULVZ model in the epicentral distance range from 111° to 113°.…”
Section: Axisem3d Synthetic Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning methodologies are becoming more prevalent in the geosciences (for a review see: Bower et al, 2013) and seis-mology (for a review see: Kong et al, 2019) with methods used to automate data selection (e.g. Valentine & Woodhouse, 2010;Thorne et al, 2020) and extracting properties from data by mapping seismograms to lower dimensional space using autoencoders (Valentine & Trampert, 2012) or sequence seismograms and identify features such as the precense of seismic scatterers (Kim et al, 2020). Here we use an unsupervised learning algorithm as part of our automation technique.…”
Section: Introductionmentioning
confidence: 99%